"DO NOT LET LAURELS CARRY YOU AWAY, THEY ARE CHEAP STUFF..." (VAVILOV’S ROLE IN THE FORMATION OF G. D. KARPECHENKO AS A LEADER OF GENETIC RESEARCH AT VIR) - M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
On the basis of the correspondence between N. I. Vavilov and G. D. Karpechenko in 1924-1926, their working relationship during this period has been analyzed. G. D. Karpechenko had just become head of a newly established genetics laboratory at Vavilov’s institute, and the director tried to help him to understand the tasks and research methodology. As a result, for the years ahead, theoretical justification and experimental implementation of new methods of breeding material development was identified. A comprehensive genetic study of the collection of plant genetic resources was made, and its further utilization in practical breeding work with major agricultural crops was worked out.